2016
DOI: 10.1021/acs.macromol.6b00325
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Stereospecific Polymerization of a Novel Bulky Styrene Derivative

Abstract: A novel vinylbiphenyl monomer, 2-methoxy-5-phenyl­styrene (MOPS), was designed and efficiently synthesized to investigate the stereospecific polymerization of bulky and polar styrenic derivative. Regardless of its large side group and electron-donating o-methoxy substituent, this compound showed a high polymerizability and was readily converted to the corresponding polymers with moderate to high molecular mass through radical, anionic, and coordination polymerizations. The resultant polymers were characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 59 publications
(102 reference statements)
0
15
0
Order By: Relevance
“…As a significant breakthrough, Cui and Hou respectively reported the homopolymerization of polar methoxystyrene with a perfect stereoselectivity using Group 3 (rare-earth metal) catalysts for the first time. Mechanistic insights revealed that the chelation of polar methoxy group of monomer to the metal center does not poison the active species but unexpectedly lowers the coordination and insertion energies of the methoxystyrene monomer, thus, facilitating its polymerization. This milestone finding opened the mysterious box of homopolymerization of a broad scope of polar styrenes. Furthermore, this approach has been extended to the copolymerization of ethylene and polar styrenes using Group 3 and 4 catalysts. However, it is noteworthy that functional groups on polar styrenes applied to ethylene copolymerization are generally limited to the alkyloxy, alkylthio, amino, phosphine, and halide moieties at meta- and para-positions. In contrast, the utilization of more challenging ortho-substituted (closer to the reactive double bond) polar styrenes with a broader scope of functional groups is still an open research area.…”
Section: Introductionmentioning
confidence: 99%
“…As a significant breakthrough, Cui and Hou respectively reported the homopolymerization of polar methoxystyrene with a perfect stereoselectivity using Group 3 (rare-earth metal) catalysts for the first time. Mechanistic insights revealed that the chelation of polar methoxy group of monomer to the metal center does not poison the active species but unexpectedly lowers the coordination and insertion energies of the methoxystyrene monomer, thus, facilitating its polymerization. This milestone finding opened the mysterious box of homopolymerization of a broad scope of polar styrenes. Furthermore, this approach has been extended to the copolymerization of ethylene and polar styrenes using Group 3 and 4 catalysts. However, it is noteworthy that functional groups on polar styrenes applied to ethylene copolymerization are generally limited to the alkyloxy, alkylthio, amino, phosphine, and halide moieties at meta- and para-positions. In contrast, the utilization of more challenging ortho-substituted (closer to the reactive double bond) polar styrenes with a broader scope of functional groups is still an open research area.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, extensive studies have been devoted to develop efficient “single‐site” catalytic systems for stereospecific polymerization of styrene and its derivatives, and various homogeneous metallocene, half‐metallocene, and non‐metallocene group 3 and 4 metal‐based catalysts have been invented . In the meantime, syndiotactic polystyrene derivatives bearing polar groups such as halogen, alkoxyl, aminoalkyl, and methylthio etc., that provide polymers with improved surface properties, adhesive properties, affinity for dyes, and compatibility with other polar polymers, have been successfully prepared …”
Section: Methodsmentioning
confidence: 99%
“…Recently, we found that rare‐earth metal catalysts supported by pyridyl methyl fluorenyl ligand demonstrated their superiority on selective and controlled coordination polymerization of styrene derivatives bearing various electron‐donating/withdrawing substituents . With the help of these powerful constrained geometry configuration (CGC) catalysts, we successfully synthesized a series of high syndiotactic polystyrene derivatives such as poly(methoxystyrene), poly(4‐Methylthiostyrene), poly(4‐fluorostyrene) etc . In this contribution, we report that coordination polymerizations of 1VN, 2VN, and MVN were carried out by using the half‐sandwich scandium precursor 1 and the CGC rare‐earth metal precursors 2a ‐ 2c ( Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…The coordination (co)­polymerization of polar olefins to prepare high functional polyolefins having superior surface properties, adhesion properties, and compatibility with other types of materials has always been a challenging and high-profile issue in academia and industry. The most serious difficulty lies in the fact that the high oxyphilic early transition metal catalysts can be easily poisoned by polar olefins because the stronger Lewis basic heteroatom groups of polar olefins have more preferential coordination ability than the weaker Lewis basic double bond to the strong Lewis acidic metal centers. Subsequently, the low oxyphilic late transition metal catalysts, which are more tolerant of heteroatom functionalities in the monomer and the polymer, have ascended on the history stage and gradually began to open up new areas for the coordination (co)­polymerization of polar olefins such as polar norbornene, acrylates, vinyl ethers, vinyl acetate, vinyl halides, acrylonitrile, CO, etc. Recently, a significant breakthrough in the coordination (co)­polymerization of polar olefins has been made by the high oxyphilic rare-earth metal catalysts. Activated by a catalytically equimolar amount of cocatalyst borate and/or an excess of AlR 3 , rare-earth metal alkyl cations [LLnR] + generated from a series of rare-earth metal dialkyl complexes LLnR 2 L' n (Ln is a rare earth metal center, L is a negative monovalent multi-dentate supporting ligand, R is a negative monovalent alkyl ligand, L' n is a neutral ligand like tetrahydrofuran (THF) solvent molecules with a number in the range of 0–2) exhibit high activities and stereoselectivities in the coordination (co)...…”
Section: Introductionmentioning
confidence: 99%